Method for removing silicon in phosphogypsum
Through the synergistic effect of using aminolated composite aerogel in phosphogypsum treatment, the problem of efficient desorption of silicon in phosphogypsum is solved, and the low-energy consumption and environmentally friendly treatment effect is achieved, and the product purity and treatment efficiency are improved.
Patent Information
- Application Number
- CN202411584384.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art has problems of high energy consumption, environmental pollution and unstable product purity when treating phosphogypsum, especially the high wear and maintenance costs of equipment under high temperature conditions caused by pyrolysis, and the wastewater treatment problems caused by the flotation process have not been solved. .
By putting an aminolated composite aerogel, the synergistic effect between materials is used to achieve silicon desorption in phosphogypsum. Specific steps include crushing and sieving the phosphogypsum, pickling and centrifugal filtration, drying at low temperature and mixing it with the alkaline extract for heating, adjusting the pH value and adding an aminolated composite aerogel.
It has achieved efficient and environmentally friendly removal of silicon elements in phosphogypsum, reducing energy consumption and environmental pollution, and the product is stable in purity and low subsequent treatment costs.
Smart Images

Figure BDA0005123944480000121 
Figure HDA0005123944490000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental protection, and in particular to a method for harmlessly removing silicon from phosphogypsum. Background Art
[0002] Phosphogypsum is the main byproduct of phosphate fertilizer production. Hundreds of millions of tons of phosphogypsum are produced worldwide each year, and most of it is piled up in open air, causing serious environmental problems. These piled-up phosphogypsum not only occupies a large amount of land resources, but also may pollute groundwater, soil and air. Especially under rain erosion, harmful substances in phosphogypsum such as heavy metals, fluorides and residual phosphates will penetrate into the environment, causing long-term ecological threats. In addition, the main component of phosphogypsum is calcium sulfate dihydrate, which has stable chemical properties and is difficult to achieve harmless treatment through simple physical or chemical means, which further increases the difficulty of its resource utilization. Although some existing treatment technologies, such as acidolysis and pyrolysis, can achieve resource utilization to a certain extent, they still face a series of technical bottlenecks and economic constraints in practical applications. For example, the acidolysis method easily produces a large amount of acidic wastewater, and the treatment cost is high; although the pyrolysis method can effectively separate the silicon element in phosphogypsum, its process requires a relatively high temperature (usually above 1000°C), which makes the energy consumption extremely high. In addition, harmful gases such as sulfur dioxide are easily generated during the pyrolysis process, which is not good for the environment and requires an additional tail gas treatment system. Under high temperature conditions, the wear and maintenance costs of the equipment are also high, which further limits the large-scale application of this technology. Furthermore, the purity of the products of the pyrolysis method is also unstable, and the subsequent processing costs are high. The existing invention patent (CN117861862 A) uses a co-reverse flotation process to reduce the silicon content in phosphogypsum, but the problem of wastewater treatment generated by the flotation process has not been solved. Therefore, it is urgent to develop a new process that can remove silicon from phosphogypsum in an efficient and environmentally friendly manner. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a method for removing silicon from phosphogypsum, by adding amino composite aerogel and utilizing the synergistic effect between materials to achieve the desorption of silicon from phosphogypsum.
[0004] Technical solution: A method for removing silicon from phosphogypsum comprises the following steps: S1. crushing, screening, pickling and centrifugal filtering of phosphogypsum; S2. Low-temperature drying of the pretreated phosphogypsum in S1; S3. The dried phosphate gypsum obtained in S2 is mixed with the alkaline extract and heated with stirring. After cooling to room temperature, the pH value of the solution is adjusted and the amino-modified composite aerogel is added to achieve silicon desorption. Preferably, the particle size of the phosphogypsum after crushing and screening in S1 is 1 to 3 mm, the pickling solution is dilute sulfuric acid with a concentration of 0.1 to 0.5 mol / L, and the pickling time is 60 to 80 min. Preferably, the temperature of the low-temperature drying in S2 is 30-50° C. and the time is 60-120 min. Preferably, the alkaline extract in S3 is a NaOH solution with a concentration of 0.5 to 1 mol / L, the mass ratio of phosphogypsum to the alkaline extract is 1:5 to 10, the heating reaction temperature is 80 to 100°C, the heating time is 2 to 5 hours, and the pH value of the solution is adjusted to 3 to 5. Preferably, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. adding a chitosan / acetic acid solution having a mass fraction of 2.5 wt % to a magnetic graphene oxide suspension having a concentration of 4 mg / ml, and stirring to obtain a suspension; S12. The suspension obtained in S11 was heated to 100-130° C. and then cooled to room temperature, and then freeze-dried at -50--40° C. for 40-50 h to obtain an initial aerogel; S13. The initial aerogel obtained in S12 and polyethyleneimine were added to methanol in a mass ratio of 1-4:3-6, heated at 60°C for 3h after ultrasonication, and then reacted at 80°C for 1-2h to obtain an amino aerogel; S14. The short-cut electrospun fiber suspension is vacuum filtered onto the amino aerogel skeleton obtained in S13, and then dried at 40-60° C. for 6 h to obtain the amino composite aerogel. Preferably, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension in S11 is 1-7:3-15. Preferably, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2-6:0.5-2, and obtaining a mixed suspension after stirring and ultrasonication; S22. The mixed suspension is placed in a container and reacted at 180° C. for 12 h, followed by soaking and washing to obtain magnetic graphene oxide. Preferably, the preparation of the chopped electrospun fiber suspension in S14 comprises the following steps: S31. The carboxylated montmorillonite was added to an acetic acid solution and ultrasonically dispersed, followed by addition of chitosan and copper chloride, and stirred thoroughly to obtain a solution having a mass fraction of 8 to 15 wt %; S32. The solution obtained in S31 was electrospun at a voltage of 15 to 25 kV, a flow rate of 0.8 to 1.5 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Add short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 3 to 10:2 to 6:1 to 3 into water and ultrasonicate to obtain a short-cut electrospun fiber suspension with a mass fraction of 3 to 8 wt%. Preferably, the mass ratio of carboxylated montmorillonite, chitosan and copper chloride in S31 is 1-2:10-15:1-3. Preferably, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. Dispersing acidified montmorillonite and trimethoxysilane in ethanol at a mass ratio of 2 to 4:3 to 7, stirring at 60° C. for 8 h, washing and drying to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 1 to 3: 4 to 7: 2 to 6 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60° C. under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite. Preferably, in one embodiment, the recycling of the amino-modified composite aerogel comprises the following steps: S1-1. The aminated composite aerogel is added to a NaOH solution having a concentration of 0.05 to 0.1 mol / L and soaked for 6 to 10 hours, wherein the mass ratio of the aminated aerogel to the NaOH solution is 1 to 3: 100 to 400; S1-2. The aminated composite aerogel treated with NaOH solution in S1-1 is added into water and ultrasonicated for 20 to 40 minutes to obtain a recovered aminated composite aerogel. Beneficial effects: 1. The short electrospun fibers of the present invention contain Cu 2+ Ion, Cu 2+ The ions mainly use complexation to drive silicates to diffuse from the liquid to the surface of the amino-modified composite aerogel, thereby inducing silicates to bind to multiple NH2 groups, and Cu 2+ ions as loaded metals can provide additional strong active sites to improve adsorption performance. 2+The ions are embedded in the short-cut electrospun fibers and slowly released to the fiber surface during the adsorption process, which prolongs the service life of the material. The short-cut electrospun fibers are also loaded with carboxylated montmorillonite. The carboxylation modification can improve the dispersibility of montmorillonite in the solution and reduce the agglomeration phenomenon. It increases the surface area in contact with the anions and enhances the electrostatic effect, thereby improving the adsorption efficiency. 2. In the present invention, some of the short-cut electrospun fibers are attached to the pores of the amino-modified composite aerogel. The three-dimensional network structure of the aerogel can support the short-cut electrospun fibers and increase the mechanical stability. At the same time, the pores of the aerogel can provide a path for the adsorbed molecules, and the short-cut electrospun fibers attached to the pores of the aerogel can serve as a supplementary adsorption material for the aerogel. The two work together to improve the adsorption performance of the amino-modified composite aerogel. 3. In the present invention, succinic anhydride is used to modify polyvinyl alcohol, so that succinic anhydride and polyvinyl alcohol can undergo an esterification reaction, thereby reducing the hydroxyl groups on the side chains of the polyvinyl alcohol molecules to form hydrophobic ester bonds, thereby improving the water resistance of the polyvinyl alcohol film, and further improving the stability of the amino composite aerogel; 4. In the present invention, the magnetism of aerogel can be used to realize the recovery of aerogel. After being soaked in alkaline solution and ultrasonically cleaned, the amino composite aerogel can be reused, which has environmentally friendly characteristics. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is the retention rate of the adsorption capacity of the sample after being recycled for 5 times. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A method for removing silicon from phosphogypsum comprises the following steps: S1. The phosphogypsum was crushed and screened, washed with 0.1 mol / L dilute sulfuric acid for 60 min, and then centrifuged to obtain phosphogypsum particles with a particle size of 1 mm; S2. Dry the pretreated phosphogypsum in S1 at 30°C for 60 min; S3. The dried phosphate gypsum obtained in S2 was mixed with a 0.5 mol / L NaOH solution, the mass ratio of phosphate gypsum to NaOH solution was 1:5, heated at 80°C for 2h, cooled to room temperature, the pH value of the solution was adjusted to 3, and the amino-modified composite aerogel was added to achieve silicon desorption; Wherein, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. Adding a chitosan / acetic acid solution with a mass fraction of 2.5 wt% to a magnetic graphene oxide suspension with a concentration of 4 mg / ml, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension is 1:3, and stirring to obtain a suspension; S12. The suspension obtained in S11 is heated to 100°C and then cooled to room temperature, and then freeze-dried at -50°C for 40 hours to obtain an initial aerogel; S13. The initial aerogel obtained in S12 and polyethyleneimine were added to methanol in a mass ratio of 1:3, heated at 60°C for 3h after ultrasonication, and then reacted at 80°C for 1h to obtain an amino aerogel; S14. The short electrospun fiber suspension was vacuum filtered onto the amino aerogel skeleton obtained in S13, and dried at 40°C for 6h to obtain an amino composite aerogel; Wherein, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2:0.5, and obtaining a mixed suspension after stirring and ultrasonication; S22. placing the mixed suspension in a container at 150° C. for 10 h, and then soaking and washing to obtain magnetic graphene oxide; Wherein, the preparation of the short-cut electrospinning suspension in S14 comprises the following steps: S31. Carboxylated montmorillonite is added to an acetic acid solution and dispersed by ultrasonication, and then chitosan and copper chloride are added, the mass ratio of carboxylated montmorillonite, chitosan and copper chloride is 1:10:1, and after sufficient stirring, a solution with a mass fraction of 8 wt% is obtained; S32. The solution obtained in S31 was electrospun at a voltage of 15 kV, a flow rate of 0.8 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Adding short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 3:2:1 into water and ultrasonicating to obtain a short-cut electrospun fiber suspension with a mass fraction of 3 wt %; Wherein, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. Dispersing acidified montmorillonite and trimethoxysilane in a mass ratio of 2:3 in ethanol, stirring at 60° C. for 8 h, washing and drying to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 1:4:2 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60°C under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite. Example 2 A method for removing silicon from phosphogypsum comprises the following steps: S1. The phosphogypsum was crushed and screened, washed with 0.5 mol / L dilute sulfuric acid for 80 min, and then centrifuged to obtain phosphogypsum particles with a particle size of 3 mm; S2. heating the pretreated phosphogypsum in S1 at 50°C for 120 min; S3. The dried phosphate gypsum obtained in S2 was mixed with a 1 mol / L NaOH solution and heated at 100°C for 5 h. After cooling to room temperature, the pH value of the solution was adjusted to 5, and the amino-modified composite aerogel was added to achieve silicon desorption; Wherein, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. Add a chitosan / acetic acid solution with a mass fraction of 2.5wt% to a magnetic graphene oxide suspension with a concentration of 4mg / ml, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension is 7:15, and obtain a suspension after stirring; S12. Heat the suspension obtained in S11 to 130°C and then cool it to room temperature, and then freeze-dry it at -40°C for 50h to obtain an initial aerogel; S13. Add the initial aerogel obtained in S12 and polyethyleneimine in a mass ratio of 4:6 to methanol, heat at 60°C for 3h after ultrasonication, and then react at 80°C for 2h to obtain an amino aerogel; S14. The short electrospun fiber suspension was vacuum filtered onto the amino aerogel skeleton obtained in S13, and dried at 60°C for 6h to obtain an amino composite aerogel; Wherein, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2-6:0.5-2, and obtaining a mixed suspension after stirring and ultrasonication; S22. placing the mixed suspension in a container at 180° C. for 12 h, and then soaking and washing to obtain magnetic graphene oxide; Wherein, the preparation of the short-cut electrospinning suspension in S14 comprises the following steps: S31. Carboxylated montmorillonite is added to an acetic acid solution and ultrasonically dispersed, followed by adding chitosan and copper chloride, wherein the mass ratio of carboxylated montmorillonite, chitosan and copper chloride is 2:15:3, and the solution having a mass fraction of 15 wt% is obtained after sufficient stirring; S32. The solution obtained in S31 was electrospun at a voltage of 25 kV, a flow rate of 1.5 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Adding short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 10:6:3 into water and ultrasonicating to obtain a short-cut electrospun fiber suspension with a mass fraction of 8 wt %; Wherein, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. The acidified montmorillonite and trimethoxysilane in a mass ratio of 4:7 were dispersed in ethanol, stirred at 60° C. for 8 h, washed and dried to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 3:7:6 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60°C under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite. Example 3 A method for removing silicon from phosphogypsum comprises the following steps: S1. The phosphogypsum was crushed and screened, washed with 0.3 mol / L dilute sulfuric acid for 90 min, and then centrifuged to obtain phosphogypsum particles with a particle size of 3 mm; S2. heating the pretreated phosphogypsum in S1 at 40°C for 100 min; S3. The dried phosphate gypsum obtained in S2 was mixed with a 0.8 mol / L NaOH solution and heated at 90°C for 5 h. After cooling to room temperature, the pH value of the solution was adjusted to 4, and the amino-modified composite aerogel was added to achieve silicon desorption; Wherein, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. Add a chitosan / acetic acid solution with a mass fraction of 2.5wt% to a magnetic graphene oxide suspension with a concentration of 4mg / ml, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension is 5:13, and obtain a suspension after stirring; S12. Heat the suspension obtained in S11 to 120℃ and then cool it to room temperature, then freeze-dry it at -45℃ for 45h to obtain an initial aerogel; S13. Add the initial aerogel obtained in S12 and polyethyleneimine in a mass ratio of 3:5 to methanol, heat at 60℃ for 3h after ultrasonication, and then react at 80℃ for 1.5h to obtain an amino aerogel; S14. The short electrospun fiber suspension was vacuum filtered onto the amino aerogel skeleton obtained in S13, and dried at 55°C for 6h to obtain an amino composite aerogel; Wherein, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2-6:0.5-2, and obtaining a mixed suspension after stirring and ultrasonication; S22. placing the mixed suspension in a container at 180° C. for 12 h, and then soaking and washing to obtain magnetic graphene oxide; Wherein, the preparation of the short-cut electrospinning suspension in S14 comprises the following steps: S31. Carboxylated montmorillonite is added to an acetic acid solution and ultrasonically dispersed, followed by adding chitosan and copper chloride, wherein the mass ratio of carboxylated montmorillonite, chitosan and copper chloride is 2:15:3, and the solution having a mass fraction of 15 wt% is obtained after sufficient stirring; S32. The solution obtained in S31 was electrospun at a voltage of 25 kV, a flow rate of 1.5 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Adding short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 10:6:3 into water and ultrasonicating to obtain a short-cut electrospun fiber suspension with a mass fraction of 6 wt %; Wherein, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. The acidified montmorillonite and trimethoxysilane in a mass ratio of 4:7 were dispersed in ethanol, stirred at 60° C. for 8 h, washed and dried to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 3:7:6 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60°C under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite. Example 4 A method for removing silicon from phosphogypsum comprises the following steps: S1. The phosphogypsum was crushed and screened, washed with 0.3 mol / L dilute sulfuric acid for 70 min, and then centrifuged to obtain phosphogypsum particles with a particle size of 2 mm; S2. Dry the pretreated phosphogypsum in S1 at 30°C for 60 min; S3. The dried phosphate gypsum obtained in S2 was mixed with a 0.9 mol / L NaOH solution, the mass ratio of phosphate gypsum to NaOH solution was 1:5, heated at 80°C for 2h, cooled to room temperature, the pH value of the solution was adjusted to 3, and the amino-modified composite aerogel was added to achieve silicon desorption; Wherein, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. Adding a chitosan / acetic acid solution with a mass fraction of 2.5 wt% to a magnetic graphene oxide suspension with a concentration of 4 mg / ml, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension is 1:3, and stirring to obtain a suspension; S12. The suspension obtained in S11 is heated to 100°C and then cooled to room temperature, and then freeze-dried at -50°C for 40 hours to obtain an initial aerogel; S13. The initial aerogel obtained in S12 and polyethyleneimine were added to methanol in a mass ratio of 1:3, heated at 60°C for 3h after ultrasonication, and then reacted at 80°C for 1h to obtain an amino aerogel; S14. The short electrospun fiber suspension was vacuum filtered onto the amino aerogel skeleton obtained in S13, and dried at 40°C for 6h to obtain an amino composite aerogel; Wherein, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2:0.5, and obtaining a mixed suspension after stirring and ultrasonication; S22. placing the mixed suspension in a container at 150° C. for 10 h, and then soaking and washing to obtain magnetic graphene oxide; Wherein, the preparation of the short-cut electrospinning suspension in S14 comprises the following steps: S31. adding carboxylated montmorillonite to an acetic acid solution and dispersing it by ultrasonication, then adding chitosan and copper chloride, wherein the mass ratio of carboxylated montmorillonite, chitosan and copper chloride is 2:13:1, and stirring thoroughly to obtain a solution having a mass fraction of 8 wt %; S32. The solution obtained in S31 was electrospun at a voltage of 15 kV, a flow rate of 0.8 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Adding short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 7:5:2 into water and ultrasonicating to obtain a short-cut electrospun fiber suspension with a mass fraction of 7 wt %; Wherein, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. The acidified montmorillonite and trimethoxysilane in a mass ratio of 3:5 were dispersed in ethanol, stirred at 60° C. for 8 h, washed and dried to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 2:5:6 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60°C under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite. Example 5 A method for removing silicon from phosphogypsum comprises the following steps: S1. The phosphogypsum was crushed and screened, washed with 0.3 mol / L dilute sulfuric acid for 70 min, and then centrifuged to obtain phosphogypsum particles with a particle size of 2 mm; S2. Dry the pretreated phosphogypsum in S1 at 30°C for 60 min; S3. The dried phosphate gypsum obtained in S2 was mixed with a 0.9 mol / L NaOH solution, the mass ratio of phosphate gypsum to NaOH solution was 1:5, heated at 80°C for 2h, cooled to room temperature, the pH value of the solution was adjusted to 3, and the amino-modified composite aerogel was added to achieve silicon desorption; Wherein, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. Adding a chitosan / acetic acid solution with a mass fraction of 2.5 wt% to a magnetic graphene oxide suspension with a concentration of 4 mg / ml, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension is 1:3, and stirring to obtain a suspension; S12. The suspension obtained in S11 is heated to 100°C and then cooled to room temperature, and then freeze-dried at -50°C for 40 hours to obtain an initial aerogel; S13. The initial aerogel obtained in S12 and polyethyleneimine were added to methanol in a mass ratio of 1:3, heated at 60°C for 3h after ultrasonication, and then reacted at 80°C for 1h to obtain an amino aerogel; S14. The short electrospun fiber suspension was vacuum filtered onto the amino aerogel skeleton obtained in S13, and dried at 40°C for 6h to obtain an amino composite aerogel; Wherein, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2:0.5, and obtaining a mixed suspension after stirring and ultrasonication; S22. placing the mixed suspension in a container at 160° C. for 10 h, and then soaking and washing to obtain magnetic graphene oxide; Wherein, the preparation of the short-cut electrospinning suspension in S14 comprises the following steps: S31. adding carboxylated montmorillonite to an acetic acid solution and dispersing it by ultrasonication, then adding chitosan and copper chloride, wherein the mass ratio of carboxylated montmorillonite, chitosan and copper chloride is 2:13:1, and stirring thoroughly to obtain a solution having a mass fraction of 8 wt %; S32. The solution obtained in S31 was electrospun at a voltage of 15 kV, a flow rate of 0.8 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Adding short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 8:4:3 into water and ultrasonicating to obtain a short-cut electrospun fiber suspension with a mass fraction of 5 wt %; Wherein, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. The acidified montmorillonite and trimethoxysilane in a mass ratio of 3:5 were dispersed in ethanol, stirred at 60° C. for 8 h, washed and dried to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 2:5:6 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60°C under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite. Example 6 A method for removing silicon from phosphogypsum comprises the following steps: S1. The phosphogypsum was crushed and screened, washed with 0.4 mol / L dilute sulfuric acid for 75 min, and then centrifuged to obtain phosphogypsum particles with a particle size of 2 mm; S2. Dry the pretreated phosphogypsum in S1 at 30°C for 60 min; S3. The dried phosphate gypsum obtained in S2 was mixed with a 0.6 mol / L NaOH solution, the mass ratio of phosphate gypsum to NaOH solution was 1:8, heated at 90°C for 4 h, cooled to room temperature, adjusted the pH value of the solution to 3, and added the amino composite aerogel to achieve silicon desorption; Wherein, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. Adding a chitosan / acetic acid solution with a mass fraction of 2.5 wt% to a magnetic graphene oxide suspension with a concentration of 4 mg / ml, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension is 1:3, and stirring to obtain a suspension; S12. The suspension obtained in S11 is heated to 100°C and then cooled to room temperature, and then freeze-dried at -50°C for 40 hours to obtain an initial aerogel; S13. The initial aerogel obtained in S12 and polyethyleneimine were added to methanol in a mass ratio of 1:5, heated at 60°C for 3h after ultrasonication, and then reacted at 80°C for 1.5h to obtain an amino aerogel; S14. The short electrospun fiber suspension was vacuum filtered onto the amino aerogel skeleton obtained in S13, and dried at 55°C for 6h to obtain an amino composite aerogel; Wherein, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2:0.5, and obtaining a mixed suspension after stirring and ultrasonication; S22. placing the mixed suspension in a container at 170° C. for 10 h, and then soaking and washing to obtain magnetic graphene oxide; Wherein, the preparation of the short-cut electrospinning suspension in S14 comprises the following steps: S31. adding carboxylated montmorillonite to an acetic acid solution and dispersing it by ultrasonication, then adding chitosan and copper chloride, wherein the mass ratio of carboxylated montmorillonite, chitosan and copper chloride is 2:13:1, and stirring thoroughly to obtain a solution having a mass fraction of 8 wt %; S32. The solution obtained in S31 was electrospun at a voltage of 18 kV, a flow rate of 1.2 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Adding short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 9:5:2 into water and ultrasonicating to obtain a short-cut electrospun fiber suspension with a mass fraction of 4 wt %; Wherein, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. The acidified montmorillonite and trimethoxysilane in a mass ratio of 4:5 were dispersed in ethanol, stirred at 60° C. for 8 h, washed and dried to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 2:7:6 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60°C under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite. Example 7 A method for removing silicon from phosphogypsum comprises the following steps: S1. The phosphogypsum was crushed and screened, washed with 0.4 mol / L dilute sulfuric acid for 65 min, and then centrifuged to obtain phosphogypsum particles with a particle size of 2 mm; S2. Dry the pretreated phosphogypsum in S1 at 45°C for 100 min; S3. The dried phosphate gypsum obtained in S2 was mixed with a 0.9 mol / L NaOH solution, the mass ratio of phosphate gypsum to NaOH solution was 1:8, heated at 90°C for 2h, cooled to room temperature, the pH value of the solution was adjusted to 3, and the amino-modified composite aerogel was added to achieve silicon desorption; Wherein, the preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. Adding a chitosan / acetic acid solution with a mass fraction of 2.5 wt% to a magnetic graphene oxide suspension with a concentration of 4 mg / ml, the volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension is 1:3, and stirring to obtain a suspension; S12. The suspension obtained in S11 is heated to 100°C and then cooled to room temperature, and then freeze-dried at -50°C for 40 hours to obtain an initial aerogel; S13. The initial aerogel obtained in S12 and polyethyleneimine were added to methanol in a mass ratio of 1:5, heated at 60°C for 3h after ultrasonication, and then reacted at 80°C for 1h to obtain an amino aerogel; S14. The short electrospun fiber suspension was vacuum filtered onto the amino aerogel skeleton obtained in S13, and dried at 40°C for 6h to obtain an amino composite aerogel; Wherein, the preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2:0.5, and obtaining a mixed suspension after stirring and ultrasonication; S22. placing the mixed suspension in a container at 155° C. for 11 h, and then soaking and washing to obtain magnetic graphene oxide; Wherein, the preparation of the short-cut electrospinning suspension in S14 comprises the following steps: S31. adding carboxylated montmorillonite to an acetic acid solution and dispersing it by ultrasonication, then adding chitosan and copper chloride, the mass ratio of carboxylated montmorillonite, chitosan and copper chloride being 2:13:3, and stirring thoroughly to obtain a solution having a mass fraction of 10 wt%; S32. The solution obtained in S31 was electrospun at a voltage of 15 kV, a flow rate of 0.8 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Adding short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 8:4:3 into water and ultrasonicating to obtain a short-cut electrospun fiber suspension with a mass fraction of 7 wt %; Wherein, the preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. The acidified montmorillonite and trimethoxysilane in a mass ratio of 3:5 were dispersed in ethanol, stirred at 60° C. for 8 h, washed and dried to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 3:5:5 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60° C. under a nitrogen atmosphere for 6 h to obtain carboxylated montmorillonite. Comparative Example 1 The difference between this comparative example and Example 5 is that the short-cut electrospun fibers are not deposited in the aminated composite aerogel. Comparative Example 2 The difference between this comparative example and Example 5 is that the composite aerogel is not subjected to amino modification. Comparative Example 3 The difference between this comparative example and Example 5 is that no cupric chloride is added to the short-cut electrospun fibers. Comparative Example 4 The difference between this comparative example and Example 5 is that no carboxylated montmorillonite is added to the short-cut electrospun fibers. Comparative Example 5 The difference between this comparative example and Example 5 is that uncarboxylated montmorillonite is added to the short-cut electrospun fibers. Comparative Example 6 The difference between this comparative example and Example 5 is that succinic anhydride is not added to the chopped electrospun fiber suspension. Performance Testing The adsorption performance and recyclability performance of the samples prepared in Examples 1-7 and Comparative Examples 1-6 of the present invention were tested, and the results are shown in Table 1. Table 1 Adsorption performance and recyclability of each sample Note: In the cycle experiment, the concentration of the NaOH solution used was 0.05 mol / L, the immersion time was 8 h, the mass ratio of the amino aerogel to the NaOH solution was 1:200, and the ultrasonic time was 30 min. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for removing silicon from phosphogypsum, characterized in that: The following steps are involved: S1. crushing, screening, pickling and centrifugal filtering of phosphogypsum; S2. Low-temperature drying of the pretreated phosphogypsum in S1; S3. The dried phosphate gypsum obtained in S2 is mixed with the alkaline extract and heated with stirring. After cooling to room temperature, the pH value of the solution is adjusted and the amino-modified composite aerogel is added to achieve silicon desorption.
2. The method for removing silicon from phosphogypsum according to claim 1, characterized in that: The particle size of the phosphogypsum after crushing and screening in S1 is 1 to 3 mm, the pickling solution is dilute sulfuric acid with a concentration of 0.1 to 0.5 mol / L, and the pickling time is 60 to 80 min.
3. The method for removing silicon from phosphogypsum according to claim 1, characterized in that: The temperature of the low temperature drying in S2 is 30-50° C. and the time is 60-120 min.
4. The method for removing silicon from phosphogypsum according to claim 1, characterized in that: The alkaline extract in S3 is a NaOH solution with a concentration of 0.5-1 mol / L, the mass ratio of phosphogypsum to the alkaline extract is 1:5-10, the temperature of the heating reaction is 80-100°C, the heating time is 2-5h, and the pH value of the solution is adjusted to 3-5.
5. The method for removing silicon from phosphogypsum according to claim 1, characterized in that: The preparation of the amino-containing composite aerogel in S3 comprises the following steps: S11. adding a chitosan / acetic acid solution having a mass fraction of 2.5 wt % to a magnetic graphene oxide suspension having a concentration of 4 mg / ml, and stirring to obtain a suspension; S12. The suspension obtained in S11 was heated to 100-130° C. and then cooled to room temperature, and then freeze-dried at -50--40° C. for 40-50 h to obtain an initial aerogel; S13. The initial aerogel obtained in S12 and polyethyleneimine were added to methanol in a mass ratio of 1-4:3-6, heated at 60°C for 3h after ultrasonication, and then reacted at 80°C for 1-2h to obtain an amino aerogel; S14. The short-cut electrospun fiber suspension is vacuum filtered onto the amino aerogel skeleton obtained in S13, and then dried at 40-60° C. for 6 h to obtain the amino composite aerogel.
6. The method for removing silicon from phosphogypsum according to claim 5, characterized in that: The volume ratio of the chitosan / acetic acid solution to the magnetic graphene oxide suspension in S11 is 1-7:3-15.
7. The method for removing silicon from phosphogypsum according to claim 5, characterized in that: The preparation of the magnetic graphene oxide suspension in S11 comprises the following steps: S21. adding graphene oxide and cobalt acetylacetonate to an ethanol solution in sequence, wherein the mass ratio of cobalt acetylacetonate to graphene oxide is 2-6:0.5-2, and obtaining a mixed suspension after stirring and ultrasonication; S22. The mixed suspension is placed in a container and reacted at 180° C. for 12 h, followed by soaking and washing to obtain magnetic graphene oxide.
8. The method for removing silicon from phosphogypsum according to claim 5, characterized in that: The preparation of the short-cut electrospun fiber suspension in S14 comprises the following steps: S31. The carboxylated montmorillonite was added to an acetic acid solution and ultrasonically dispersed, followed by addition of chitosan and copper chloride, and stirred thoroughly to obtain a solution having a mass fraction of 8 to 15 wt %; S32. The solution obtained in S31 was electrospun at a voltage of 15 to 25 kV, a flow rate of 0.8 to 1.5 ml / h, and a receiving distance of 20 cm, and the electrospun fiber bundles were collected by parallel metal sheets; S33. The electrospun fiber bundle obtained in S32 is chopped to obtain short-cut electrospun fibers with a length of 1 to 2 mm. S34. Add short-cut electrospun fibers, PVA and succinic anhydride in a mass ratio of 3 to 10:2 to 6:1 to 3 into water and ultrasonicate to obtain a short-cut electrospun fiber suspension with a mass fraction of 3 to 8 wt%.
9. The method for removing silicon from phosphogypsum according to claim 8, characterized in that: The mass ratio of carboxylated montmorillonite, chitosan and copper chloride in the S31 is 1-2:10-15:1-3.
10. The method for removing silicon from phosphogypsum according to claim 8, characterized in that: The preparation of carboxylated montmorillonite in S31 comprises the following steps: S41. The montmorillonite was stirred in 1.0 mol / L hydrochloric acid for 12 h and then fully washed to obtain acidified montmorillonite; S42. Dispersing acidified montmorillonite and trimethoxysilane in ethanol at a mass ratio of 2 to 4:3 to 7, stirring at 60° C. for 8 h, washing and drying to obtain thiolated montmorillonite; S43. Add thiolated montmorillonite, 2-methylenesuccinic acid and benzoyl peroxide in a mass ratio of 1 to 3: 4 to 7: 2 to 6 to anhydrous ethanol, heat and stir in a constant temperature water bath at 60° C. under a nitrogen atmosphere for 6 hours to obtain carboxylated montmorillonite.
Citation Information
Patent Citations
Method for synchronous desiliconization and organic matter removal of ardealite through co-reverse flotation
CN117861862A
Cited By
Phosphogypsum purifying agent and purifying process
CN120243280A